Comparing Two Algorithms for Document Retrieval using Citation Links - Bichteler, Julie; Eaton, Edward A. (Journal of the American Society for Information Science, 1977)
This investigation compared the retrieval effectiveness of a one‐pass algorithm which employs a simple similarity calculation to that of the more complex multi‐pass Schiminovich algorithm. By means of lists of proposed relevant citations from users, searches on the AIP SPIN data base were conducted, resulting in two ordered lists of documents for each request. Recall/precision plots, based on user evaluations, illustrated that the average performance of the Schiminovich algorithm is marginally worse than that of the similarity algorithm. Thus, a relatively inexpensive procedure is sufficient to provide quite satisfactory document retrieval performance from citation data alone.